Effects of conventional interventions on early-stage primary cutaneous marginal zone lymphoma: A population-based study. (March 2022) - Liu, Hailing; Shi, Xiao; Cao, Lei; Miao, Yi; Du, Xinyi; Huang, Rong; Zhu, Han; Xu, Wei; Li, Jianyong; Fan, Lei
Abstract: Background: Information on the outcomes and treatments of early-stage (I/II) primary cutaneous marginal zone lymphoma (PCMZL) is limited. This study aimed to identify the predictors of mortality in early-stage PCMZL and compare the long-term survival of conventional approaches. Methods: We extracted data on early-stage PCMZL from the Surveillance Epidemiology and End Results (SEER) database and used Cox regression, propensity score matching (PSM), and competing risk analyses to explore the association of characteristics and therapeutic methods with survival. Results: We identified 1006 early-stage PCMZL cases between 1993 and 2016 in the SEER registry. Cox regression indicated that age over 60 years, specific primary sites (i.e., face, scalp, neck, lower limb, and hip), diagnosis before 2005, and coexisting malignancy were unfavorable predictors for overall survival (OS), while radiotherapy (RT) with or without surgery (Sx) improved OS independently. Besides, age over 60 years, diagnosis before 2005, and chemotherapy (CT) were adverse predictors for disease-specific survival (DSS). PSM analyses showed RT improved the OS and DSS rates while CT reduced the OS and DSS rates. Competing risk analyses demonstrated a significant reduction in the risk of death from PCMZL in patients treated with RT ± Sx than those receiving any CT. Conclusion: For early-stage PCMZL, RT can probably be an essential component for the initial therapy, and a combination with new drugs could be considered in future studies. Highlights: It is the largest cohort of early-stage primary cutaneous marginal zone lymphoma. Radiotherapy has the superior position in our cohort. Cox models, propensity score matching, and competing risk analysis were applied.